The effect of nanocellulose to coated paper and recycled paper - Durmaz, Ekrem; Ates, Saim; Atik, Celil (Walter de Gruyter GmbH, 2024)
Abstract This study investigated the properties of paper coated with nanocelluloses and nanocellulose-enhanced recycled paper derived from diverse waste paper sources. The grammages and thicknesses of both coated and recycled paper increased proportionally with the number of coating layers and the concentration of added cellulose nanofibrils (CNF) and cellulose nanocrystals (CNC). While the tensile index and modulus of elasticity of coated paper decreased post-coating, these properties of recycled paper improved with higher CNF concentrations, with minimal changes observed with CNC. The burst strength of coated paper increased with additional coating layers, regardless of whether CNF or CNC was used. The tear index of coated paper surpassed that of the base paper, while the burst strength of recycled paper with CNF exceeded that of CNC. Recycled paper with added nanocellulose exhibited higher tear index values than control paper, with CNF addition notably enhancing tear index compared to CNC. The types of nanocellulose significantly influenced the optical and barrier properties of both coated and recycled paper. In conclusion, this study suggests that leveraging CNF and CNC can enhance the quality of low-grade and recycled paper, potentially opening new avenues for their applications.
Keywords: properties; CNF; recycled paper; coating; CNC